Psychological traits of willingness to communicate: An assessment of students’ speaking performance - M Bambang Purwanto; Yuliana Yuliana; Habib Soleimani; Yusri Yusri (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
This study explores the relationship between psychological traits and willingness to communicate (WTC) as well as the speaking performance of students in the Department of United Kingdom, Sriwijaya State Polytechnic. The psychological characteristics studied include self-confidence, anxiety about speaking, and motivation. A quantitative descriptive approach was used to collect and analyze data from a selected sample of students. The instruments used in this study include questionnaires to measure the level of confidence, speaking anxiety, and motivation and an assessment of speaking performance through a speaking test. The study's results showed a significant correlation between psychological traits and WTC and speaking performance. The calculation results show the Personality factor: Score 85, categorized as "Medium" (Medium). Motivation (Score 82, categorized as "Medium." Communicative Competence: Score of 86, classified as "High." Learning Anxiety: Score 85, categorized as "Medium," and Self-Confidence: Score 78, categorized as "Low." High self-confidence and low speaking anxiety were positively correlated with higher WTC and better speaking performance. In addition, intrinsic and extrinsic motivation was also found to be an essential factor affecting students' active participation in oral communication activities. The conclusion of this study shows that psychological traits have an essential role in influencing students' willingness to communicate and their speaking performance. These findings provide practical implications for developing teaching strategies to improve students' speaking skills by paying attention to their psychological aspects. Advice is given to create a supportive learning environment and psychological support for needy students.